2000
DOI: 10.1007/s002390010045
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Structural Features in Class I Major Fimbrial Subunits (Pilin) in Gram-Negative Bacteria. Molecular Basis of Classification in Seven Subfamilies and Identification of Intrasubfamily Sequence Signature Motifs Which Might Be Implicated in Quaternary Structure

Abstract: Type 1 and P-pili are prototype members of Class I fimbriae produced by Gram-negative bacteria. Despite common structural characteristics, the low level of amino acid sequence conservation among the Class I major fimbrial subunits (pilins) indicates considerable evolutionary distance between members of this superfamily. We highlight here structural relatedness between Class I pilins from their two-dimensional sequence analysis using hydrophobic cluster analysis (HCA) and secondary structure predictions (PHD pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…3, underlined), which is cleaved between Ala-23 and Ala-24. Based on the amino acid sequence homology with other major subunit genes, the N-terminal region of MrxA is predicted to be involved in subunit-subunit interactions, while the C-terminal sequence (Gly-166 to Leu-179) is predicted to form a b-zipper motif recognized by PapD-like chaperones (Girardeau et al, 2000). Further proof that the mrx operon encodes the fimbriae produced on agar surfaces is obtained from a recently constructed strain in which mrxA was disrupted (He, 2002).…”
Section: Production Of Mrx Fimbriae On Agar Mediummentioning
confidence: 99%
“…3, underlined), which is cleaved between Ala-23 and Ala-24. Based on the amino acid sequence homology with other major subunit genes, the N-terminal region of MrxA is predicted to be involved in subunit-subunit interactions, while the C-terminal sequence (Gly-166 to Leu-179) is predicted to form a b-zipper motif recognized by PapD-like chaperones (Girardeau et al, 2000). Further proof that the mrx operon encodes the fimbriae produced on agar surfaces is obtained from a recently constructed strain in which mrxA was disrupted (He, 2002).…”
Section: Production Of Mrx Fimbriae On Agar Mediummentioning
confidence: 99%
“…According to the classification of Girardeau et al (2000), PixA is a member of the Ic subfamily together with E. coli PapA, Serratia marcescens SmfA and Proteus mirabilis MrpA and PmpA. The sequence signature motif in segment S1 characteristic for the Ic subfamily…”
Section: Major Pilus Subunit Pixamentioning
confidence: 99%
“…The sequence of the S1 segment of PixA is Conserved residues are shaded and residues representing the Ic subfamily sequence signature motif of the S1 segment (Girardeau et al, 2000) are indicated in bold. …”
Section: (Gxg[kt]v[ts]fxg[ts]mentioning
confidence: 99%
“…Initial alignments of pilin sequences were performed with the program ALIGN (22). These results were compared with alignments reported by Girardeau et al (13) and Krasan et al (17), alignments that were made between HifA of different strains (13), and between HifA and a minor adapter P-pilin, PapK, not the major structural pilin PapA (17). The great strength of these reference alignments is that they have taken into account additional data beyond the primary sequence, including results from biochemical, mutational, and evolutionary studies on H. influenzae pili and E. coli pili.…”
Section: Methodsmentioning
confidence: 99%
“…influenzae type b pili have structural and gene sequence similarities (4,11,13,17) to pili described as class I (18) but not to those in the type IV pilus superfamily. In particular, strong sequence similarity is found between Hib pilins and pilins that comprise P-pili (13,17). P-pili are expressed on the surface of uropathogenic Escherichia coli that cause pyelonephritis, urinary tract infections that involve the kidneys.…”
mentioning
confidence: 99%